Predictors of outcome in ICU patients with septic shock caused by Klebsiella pneumoniae carbapenemase–producing K. pneumoniae. (May 2016) - Falcone, M.; Russo, A.; Iacovelli, A.; Restuccia, G.; Ceccarelli, G.; Giordano, A.; Farcomeni, A.; Morelli, A.; Venditti, M.
Abstract: The aim of this study was to identify factors associated with mortality in intensive care unit patients with Klebsiella pneumoniae carbapenemase–producing K. pneumoniae (KPC-Kp) septic shock. A retrospective analysis of intensive care unit patients with KPC-Kp infection and septic shock observed in a large teaching hospital from November 2010 to December 2014 was performed. A total of 111 patients were included in the study. The most frequent source of infection was unknown-focus bacteraemia in 53 patients (47.7%). The rate of resistance to colistin was 51.3%; 30-day mortality was reported for 44 patients (39.6%). Surviving patients were more frequently treated with an initial therapy (within 24 hours) including two or more antibiotics displaying in vitro activity against the isolated KPC-Kp strain (41.8 vs. 18.1%, p 0.01) and were also more likely to receive a definitive therapy including two or more in vitro active antibiotics (85.1 vs. 15.9%, p <0.001). Cox regression analysis revealed that a colistin-containing antibiotic regimen (hazard ratio (HR) 0.21, confidence interval (CI) 95% 0.05–0.72, p <0.001), use of two or more in vitro active antibiotics as definite therapy (HR 0.08, CI 95% 0.02–0.21, p <0.001) and control of removable source of infection (HR 0.14, CI 95% 0.04–0.25, p <0.001) were associated with favourable outcome; colistin resistance (HR 8.09, CI 95% 3.14–11.23, p 0.001) and intra-abdominal source of infection (HR 2.92, CI 95% 2.11–4.12, p 0.002) were associated with death. In conclusion, use of a definitive therapy with at least two antibiotics displaying in vitro activity against the KPC-Kp isolates was the most important determinant of favourable outcome, whilst isolation of colistin-resistant strains was associated with death in septic patients with KPC-Kp infection.